(untitled) (Texas Journal of Medical Science, 2026)
Acute kidney injury (AKI) in children remains a significant cause of morbidity and mortality, particularly in resource-limited regional hospitals. This prospective observational study evaluated 74 pediatric patients with AKI admitted to the Fergana Region’s Multi-Specialty Children’s Hospital between January 2022 and June 2025. The leading etiologies included sepsis, dehydration, cardiac surgery complications, and nephrotoxic drug exposure. Most patients (79.7%) were managed conservatively, while 20.3% required renal replacement therapy, primarily peritoneal dialysis. At discharge, 60.8% achieved complete recovery, 24.3% had partial recovery, 9.5% progressed to chronic kidney disease, and 5.4% died. These outcomes demonstrate both the potential for recovery with timely intervention and the persistent risk of poor prognosis in a subset of patients. Early recognition, standardized monitoring, nephrotoxin stewardship, and capacity building in peritoneal dialysis are essential strategies to improve pediatric AKI outcomes in regional settings.